AN ORDINAL FACTOR ANALYSIS OF REQUIREMENTS AND CHALLENGES OF INFORMATION AND COMMUNICATION TECHNOLOGY SYSTEM TO TRAIN PRIVATE AGRICULTURAL INSURANCE BROKERS IN IRAN (Journal of Information and Communication Technology, 2009)
This study was conducted to identify challenges and requirements of an information and communication technology (ICT) system to train brokers. Using the ordinal factor analysis, the challenges and requirements have been classified into six factors (Human, Organisational, Technical, Social, Financial, and Legal) and four factors (instructional, technical, organisational, and cultural) respectively. Finally a conceptual framework is presented for the challenges and requirements of the ICT training system.